Effect of Adherence Therapy on Patient Satisfaction and Medication Adherence among Patients with Schizophrenia (Journal of Fatima Jinnah Medical University, 2024)
Background: Patients with schizophrenia are commonly found to be non-adherent and non-satisfied with the medication for different reasons. This study aims to determine the effectiveness of adherence therapy, based on techniques of cognitive behavioral therapy and motivational interviewing, on satisfaction and medication adherence among patients with schizophrenia.Patients and methods: The study was conducted in Psychiatry Department Sir Ganga Ram Hospital, from March to December 2021. The schizophrenia patients were diagnosed according to Diagnostic and Statistical Manual-5 criteria from the outpatient Department . Patients who were non-adherent as assessed by Drug Attitude Inventory-10 (score
Keywords: Schizophrenia; Medication adherence; Patient satisfaction; Adherence therapy; PSQ-18; DAI-10